Determinants of Acceptance Takaful Insurance in Malaysia - BaitiShafee, Nur; Suhaimi, Shadia; Hashim, Haniza; Nurul Huda Mohamad, Siti; Sal Salbila Mohamed, Zuraina; Yon Wei, Lau (International Journal of Psychosocial Rehabilitation, 2020)
The Malaysian Takaful industry has shown a continuous upward achievement trend in 2018 in promoting the Takaful protection value. It shows Malaysians are familiar with the Takaful concept that leads to the rising Takaful industry performance, reflecting a greater acceptance among Malaysians towards Takaful protection plans. The advancement and consideration given to this industry and the rising chance of the business have pulled in the conventional bank and conventional insurance to incorporate Takaful principle products into their business. This research is done to analyze the factors that contribute to the acceptance of Takaful in Malaysia. The researcher distributed a questionnaire to 200 respondents from various locations to get the required information. To test the relationship between the factors, “Statistical Package of Social Science (SPSS)” is performed by the researcher. The findings of this research show the key determinants that influence customer acceptance towards Takaful have been proven to be subjective norms, the amount of information, and service qualities that have a significant effect on customer acceptance towards Takaful. Based on the finding from this research, it is expected to contribute to the current literature in order to gain better understanding on the determinant factors that lead to Takaful acceptance of Malaysian users.